2011
DOI: 10.1111/j.1740-8709.2010.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

High dietary ratio of omega‐6 to omega‐3 polyunsaturated acids during pregnancy and prevalence of post‐partum depression

Abstract: Observational studies suggest association between low concentrations of omega-3 family fatty acids and greater risk for post-partum depression (PPD). The objective was to investigate the effect of unbalanced dietary intake of omega-6/omega-3 ratio >9:1 in the prevalence for PPD. The study comprises a prospective cohort with four waves of follow-up during pregnancy and one following delivery. PPD was evaluated according to the Edinburgh Post-partum Depression Scale (PPD ≥ 11) in 106 puerperae between 2005 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(48 citation statements)
references
References 38 publications
0
47
0
1
Order By: Relevance
“…Compared to another study conducted in Rio de Janeiro, the women in this study presented a less favorable profile, in respect of the intake of alpha-linolenic fatty acid, with a median and interquartile range of 1.63 (1.25-2.19) grams versus 2.1 (1.4-2.6) grams [8]. The background social context is relevant to the intake of these nutrients, possibly through consideration of specific culinary cultures.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Compared to another study conducted in Rio de Janeiro, the women in this study presented a less favorable profile, in respect of the intake of alpha-linolenic fatty acid, with a median and interquartile range of 1.63 (1.25-2.19) grams versus 2.1 (1.4-2.6) grams [8]. The background social context is relevant to the intake of these nutrients, possibly through consideration of specific culinary cultures.…”
Section: Discussionmentioning
confidence: 74%
“…Additionally, studies on outcomes related to the intake of omega-3 fatty acids include the effects on the mother's mental health, with lower intake related to an increased risk of depressive symptoms during gestation [7], and a relationship between a 9:1 ratio of linoleic and alpha-linolenic fatty acids intake and postpartum depression [8]. Docohexanoic acid supplementation during pregnancy was associated with a higher level of attention in children at five years of age [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although heterogeneity among included studies makes it difficult to synthesize the findings, our narrative approach indicates a null benefit of n-3 PUFAs on depressive symptoms postpartum, as only one small pilot trial (Freeman et al, 2006), one weak ecological study (Hibbeln, 2002), and four small cohort and cross-sectional studies (da Rocha & Kac, 2012;De Vriese, Christophe, & Maes, 2003;Markhus et al, 2013;Otto, De Groot, & Hornstra, 2003) reported promising results, whilenone of the RCTs identified in this review showed an association of n-3 PUFAs with a decreased risk for maternal PPD.…”
Section: Discussion (Narrative Synthesis: Element 3)mentioning
confidence: 99%
“…Of the former, six were randomized controlled trials (Doornbos et al, 2009;Freeman et al, 2008;Llorent et al, 2003;Makrides et al, 2010;Mozurkewich et al, 2013;Rees, Austin, & Parker, 2008) and two pilot trials (Freeman et al, 2006;Marangell et al, 2004). The nine observational studies included: one ecological study (Hibbeln, 2002), a cross-sectional study (De Vriese, Christophe, & Maes, 2003), a case-control study (Browne, Scott, & Silvers, 2006), and six cohort studies (da Rocha & Kac, 2012;Markhus et al, 2013;Miyake et al, 2006;Otto, De Groot, & Hornstra, 2003;Parker et al, 2014;Strøm, Mortensen, Halldorsson, Thorsdottir, & Olsen, 2009). The included studies and the results of our quality appraisals are summarized in Table A1, while more detail on the characteristics of the studies is presented in Table A2.…”
Section: Overall Results In Context With Expectations Arising From Thmentioning
confidence: 99%
“…It becomes harder to monitor and to treat this disease, because women often neglect PPD symptoms. 8 It is essential to take preventive measures by defining whether postpartum depression is a separate type of depression and time of detection as well as factors related to prepartum depression. From an etiological point of view, depressive disorders are a heterogeneous group and make up the last stage of many different causal pathways.…”
Section: Introductionmentioning
confidence: 99%